Clinical evolution of pure upper motor neuron disease/dysfunction (PUMMD). Issue 1 (21st November 2012) - D'amico, Emanuele; Pasmantier, Meredith; Lee, Yei‐won; Weimer, Louis; Mitsumoto, Hiroshi
Abstract Introduction: PLS is defined as pure upper motor neuron disease/dysfunction (PUMND) beyond 48 months after symptom onset. We know little about its early stages, but such knowledge would help to identify the mechanisms underlying PLS and ALS and determine why PLS patients seem to be protected against lower MND (LMND). Methods: We reviewed 622 MND cases during a 4‐year period and identified 34 patients with PUMND (5.4%). Results: Among 23 cases with follow‐up data/electromyograms (EMGs; 2 had only 1 EMG), 13 (57%) remained classified as PUMND, and 8 (35%) developed LMND (mean, 51.4 months after onset). Of these 8, LMND developed in 3 after 48 months from symptom onset. Patients with PUMND and LMND were more functionally impaired (P = 0.02). Separately, we identified 5 patients with PUMND who developed LMND long after 48 months (range, 50–127 months). Conclusions: PLS belongs to the ALS spectrum, and perhaps all cases eventually develop LMND. Muscle Nerve, 2013